2004
DOI: 10.1242/jeb.01314
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cone visual pigments and the potential for trichromatic colour vision in two species of elasmobranch

Abstract: SUMMARY Elasmobranchs (sharks, skates and rays) are the modern descendents of the first jawed vertebrates and, as apex predators, often occupy the highest trophic levels of aquatic (predominantly marine) ecosystems. However, despite their crucial role in the structure of marine communities, their importance both to commercial and to recreational fisheries, and the inherent interest in their role in vertebrate evolution, very little is known about their visual capabilities, especially with regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 31 publications
4
87
0
1
Order By: Relevance
“…Moreover, colour-opponent responses were recorded from horizontal cells in the retina of the red stingray, Dasyatis akajei (Toyoda et al, 1978), and recent MSP studies have reported the presence of up to three spectrally distinct cone types in three ray species, including G. typus (Hart et al, 2004;Theiss et al, 2007). The results obtained from the present study suggest that G. typus, and most likely other rays with multiple cone types, are capable of discriminating a coloured reward stimulus from a range of different coloured distracter stimuli of varying brightness.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, colour-opponent responses were recorded from horizontal cells in the retina of the red stingray, Dasyatis akajei (Toyoda et al, 1978), and recent MSP studies have reported the presence of up to three spectrally distinct cone types in three ray species, including G. typus (Hart et al, 2004;Theiss et al, 2007). The results obtained from the present study suggest that G. typus, and most likely other rays with multiple cone types, are capable of discriminating a coloured reward stimulus from a range of different coloured distracter stimuli of varying brightness.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first conclusive behavioural evidence that any elasmobranch species possesses colour vision. Experiments are underway to investigate the dimensionality of colour vision of G. typus and establish whether this species has a trichromatic visual system based on the three cone types identified using MSP (Hart et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To some extent, this is due to evolutionary differences in the vertebrate eye itself such as spatial or temporal sampling or resolving power (e.g., mammals : Coimbra, Hart, Collin, & Manger, 2013;Hughes, 1977;Mengual, García, Segovia, & Pertusa, 2015;birds: Coimbra, Nolan, Collin, & Hart, 2012;Fite & Rosenfield-Wessels, 1975;Hodos & Leibowitz, 1977;elasmobranchs: Hueter, 1990;Lisney & Collin, 2007Ryan, Hart, Collin, & Hemmi, 2016;Ryan, Hemmi, Collin, & Hart, 2017;Theiss, Collin, & Hart, 2010), cone monochromacy or multichromacy (for review see Osorio & Vorobyev, 2008; see also Bedore et al, 2013;Hart, Lisney, Marshall, & Collin, 2004;Hart, Theiss, Harahush, & Collin, 2011;Van-Eyk, Siebeck, Champ, Marshall, & Hart, 2011), photoreceptor topography (Collin, 1999(Collin, , 2008, the composition of the dioptric system (Collin & Collin, 2001;Hueter et al, 2001;Sivak, 1990) or other adaptive ocular specializations. Moreover, there are differences in the neural processing of visual information in the brain.…”
mentioning
confidence: 99%